Efektifitas Pemberian Ubi Jalar Ungu Terhadap Lingkar Lengan Atas (LILA) pada Ibu Hamilwilayah Kerja Puskesmas Menggala Kabupaten Tulang Bawang Tahun 2024 - Trisia, Dina; Hervidea, Radella; Jayadi, Ajib (CV. Rayyan Dwi Bharata, 2025)
Based on data from the Menggala Health Center in 2021, the number of pregnant women with KEK was 46, in 2022 there were 57 and in 2023 there were 68 pregnant women with KEK. The purpose of this study was to determine the effectiveness of giving purple sweet potatoes on the upper arm circumference (LILA) in pregnant women in the Menggala Health Center work area of Tulang Bawang Regency in 2024. This type of research is quantitative with a Pre-experimental design with a One Group Pretest - Posttest Design approach. The time of this research was carried out on July 8-28, 2024 in the Menggala Health Center area. The population in this study were 85 pregnant women, while the sample was 85 pregnant women. The sampling technique used the total population. The independent variable in this study is the provision of purple sweet potatoes while the dependent variable in this study is the upper arm circumference (LILA) in pregnant women. The data analysis used was univariate and bivariate analysis. The bivariate analysis used was the dependent sample with the paired samples statistics test. The conclusion is that there is an effectiveness of giving purple sweet potatoes on the upper arm circumference (LILA) p value is of 0.000 0.05 and body mass index (BMI) p value is of 0.000 0.05 in pregnant women in the Menggala Health Center working area of Tulang Bawang Regency in 2024. Suggestions: The Menggala Health Center provides counseling on the importance of providing additional food and utilizing local foods as PMT for pregnant women, one of which is purple sweet potatoes.